Cloning and expression of the HpaI restriction-modification genes. - Ito, H (1992)
The genes from Haemophilus parainfluenzae encoding the HpaI restriction-modification system were cloned and expressed in Escherichia coli. From the DNA sequence, we predicted the HpaI endonuclease (R.HpaI) to have 254 amino acid residues (Mr 29,630) and the HpaI methyltransferase (M.HpaI) to have 314 amino acid residues (37,390). The R.HpaI and M.HpaI genes overlapped by 16 base pairs on the chromosomal DNA. The genes had the same orientation. The clone, named E. coli HB101-HPA2, overproduced R.HpaI. R.HpaI activity from the clone was 100-fold that from H. parainfluenzae. The amino acid sequence of M.HpaI was compared with those of other type II methyltransferases.